Breaking barriers for a bio-based economy: Interactive reflection on monitoring water quality. Issue 74 (August 2017) - Metze, Tamara; Schuitmaker, Tjerk Jan; Bitsch, Lise; Broerse, Jacqueline
Highlights: Systemic barriers for water monitoring impede a transition to a bio-based economy. This study adds a framing perspectives to the transition-literature. Approaching the systemic barriers discursively helps to overcome them. In a dialogue interactive reflectivity was created about framing of water-quality. Systemic change remains difficult as actors feel incapable of addressing barriers. Abstract: In a transition to a bio-based economy new ways of monitoring waste-streams and water quality can then contribute to sustainable production processes. As niche innovation, new ways of monitoring face systemic barriers. The present article examines how barriers to change manifest in discursive practices with differing normative attachments and implications. A frame analysis revealed two competing frames: (1) the dominant 'norm water' frame in which thresholds of chemical compounds are used to set policy targets; and (2) the contesting 'living water' frame, which entails innovative continuous monitoring tools that take into account the ecological effects of chemical compounds. We introduce the concept of interactive reflectivity, as a discursive tool, to collaboratively visualize, scrutinize and overcome discursive barriers to innovations. The stakeholder dialogue shows how systemic barriers are uttered discursively in niches – or other forms of responsible research and innovation – and may hinder change even at the niche-level.